2019
DOI: 10.1149/2.0391905jes
|View full text |Cite
|
Sign up to set email alerts
|

Editors' Choice—The Photoelectrochemical and Photocatalytic Properties of Tantalum Oxide and Tantalum Nitride

Abstract: The surfactant-assisted synthesis of tantalum oxide nanoparticles (Ta 2 O 5 ), its subsequent nitridation to form tantalum nitride (Ta 3 N 5 ), and the evaluation of the photoactivity of these nanoparticles, are presented. The surface, optical, and compositional characterization of the in-house synthesized photocatalysts indicate spherical nanoparticles with φ = 30 nm Ta 2 O 5 and φ = 30 nm Ta 3 N 5 with the latter photocatalysts showing absorbance onset at ∼ 630 nm. Photoelectrochemical analysis of the variou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 41 publications
0
5
0
Order By: Relevance
“…Further, from our previous studies, the use of glacial acetic acid has indicated the formation of oxides with a high surface area that maintain stability [64]. Besides, ethoxide precursors have reportedly been known for interactions resulting in stable complexes with metal cations in acidic media [63,65]. Based on these references, in our previous work, we investigated the use of an ethoxide precursor with glacial acetic acid implementing the sol-gel process [63].…”
Section: Synthesis Approachmentioning
confidence: 99%
See 2 more Smart Citations
“…Further, from our previous studies, the use of glacial acetic acid has indicated the formation of oxides with a high surface area that maintain stability [64]. Besides, ethoxide precursors have reportedly been known for interactions resulting in stable complexes with metal cations in acidic media [63,65]. Based on these references, in our previous work, we investigated the use of an ethoxide precursor with glacial acetic acid implementing the sol-gel process [63].…”
Section: Synthesis Approachmentioning
confidence: 99%
“…Besides, ethoxide precursors have reportedly been known for interactions resulting in stable complexes with metal cations in acidic media [63,65]. Based on these references, in our previous work, we investigated the use of an ethoxide precursor with glacial acetic acid implementing the sol-gel process [63]. We studied the complete nitridation of as-synthesized Ta 2 O 5 crystals in the same work to achieve single phase Ta 3 N 5 , and herein we present a novel partial nitridation technique to achieve single phase TaON.…”
Section: Synthesis Approachmentioning
confidence: 99%
See 1 more Smart Citation
“…Tantalum pentoxide (Ta 2 O 5 , also known as tantala or tantite) has a long list of desirable properties, including a wide band gap, [1] high dielectric constant [2], low optical absorptivity [3], and high nonlinear refractive index [4]. These have resulted in its incorporation into a variety of technologies, including capacitors [5], optical coatings [6], biochemically inert devices [7], and photonic integrated circuits [8] among other applications.…”
Section: Introductionmentioning
confidence: 99%
“…The conversion of oxides to oxynitrides is a well-established method for particulate photocatalysts to shift the band gap within the visible region [34][35][36]. Among oxynitrides, Tantalum OxyNitride (TaOxNy) show interesting performances [37][38][39][40]. Semiconductors such as TaON [41] and Ta3N5 [42,43] possess an interesting band structure,, in the ~2.2-2.7 eV range depending on the amount of N present in the structure, allowing a theoretical solar-to-hydrogen efficiency as high as 15.9% under AM 1.5 G 100 mW•cm -2 irradiation [43].…”
Section: Introductionmentioning
confidence: 99%